Hubungan Pengetahuan dan Sikap dengan Pengelolaan Sampah Masyarakat di Kecamatan Manggala Kota Makassar - Firdaus Daud (Universitas Negeri Makassar, 2022)
This study aims to analyze: knowledge of waste, attitudes towards waste, waste management, relationship of knowledge and attitudes with waste management, relationship of knowledge with waste management, relationship of attitude with community waste management in the District. Manggala, Makassar City. This research is an ex-post facto research. When examining causal relationships between variables, this type includes correlational research. Determining the sample size using the Isaac and Michael table with an error rate of 5%, the research sample was 578 households. Cluster Random Sampling Technique, 20% of the 578 households were taken, i.e. 115 samples. The results showed: 1) The knowledge of waste in the community was in the low category, 2) Attitudes towards the community's waste were in the neutral category tended to be positive, 3) Waste management in the community was in the fairly good category, 4) Knowledge of waste and attitudes towards waste together -the same has a significant relationship with waste management, 5) Knowledge of waste has a significant relationship with waste management, 6) Attitudes towards waste have a significant relationship with waste management in the community in Manggala District, Makassar City. Based on the results of the analysis and the findings obtained, it is recommended as follows: 1) It is hoped that the Makassar City government will try to increase public knowledge about waste through education and training at the RW level to the District level, 2) It is expected that the community will continue to increase their participation in the implementation of the hygiene program in each environment., 3) It is hoped that other researchers will use the research results as a reference and reference material to support further research, 4) It is hoped that this research can be useful and beneficial for all elements of society who use this research. Keyword: knowledge, attitude and waste management